1999
DOI: 10.1038/sj.gt.3300899
|View full text |Cite
|
Sign up to set email alerts
|

Human PBMC-derived dendritic cells transduced with an adenovirus vector induce cytotoxic T-lymphocyte responses against a vector-encoded antigen in vitro

Abstract: Dendritic cells (DC) are among the most potent antigentor encoding bacterial ␤-galactosidase (␤-gal) under the presenting cells known and play an important role in the transcriptional control of a CMV promoter was used to initiation of antigen-specific T-lymphocyte responses. Sevtransduce DC at multiplicities of infection (MOI) up to 1000. eral recent studies have demonstrated that DC expressing While high MOI were required to achieve efficient transducvector-encoded tumour-associated antigens can induce tion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 49 publications
4
21
0
Order By: Relevance
“…As previously shown, the adenoviral transduction did not have any influence on the maturation state of the resulting DC population. 19,[22][23][24] In mice, the use of DC infected with tumor-associated Ag for immunization and the induction of T-cellmediated protective immunity resulting in the reduction of established tumors could be demonstrated. Immunization with Ad-DC induced long-lasting antitumor activity even after single administration when compared to the direct injection of Ad-gp100 alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously shown, the adenoviral transduction did not have any influence on the maturation state of the resulting DC population. 19,[22][23][24] In mice, the use of DC infected with tumor-associated Ag for immunization and the induction of T-cellmediated protective immunity resulting in the reduction of established tumors could be demonstrated. Immunization with Ad-DC induced long-lasting antitumor activity even after single administration when compared to the direct injection of Ad-gp100 alone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most investigators used immature, peptide-pulsed or infected DC for priming and restimulation of CD8 + T cells. 22,23,[26][27][28][29] Philip et al showed that immature DC loaded with MART-1 peptide or infected with an adenoviral construct were functionally equivalent in the induction of peptide-specific CTL in vitro. 27 We have recently shown that peptide-pulsed immature DC are inferior to mature DC in inducing peptide-specific T-cell responses in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary experiments, we have observed that Adtransduced DC can effectively activate melanoma-specific CD8 + CTL in vitro, thus confirming recently published reports. 14,19 It remains to be determined how the immunosuppressive effects described in this report will impact on the induction of antigen-specific cellular immune responses with Ad-transduced DC.…”
Section: Figure 3 Adenoviral Transduction Of Mature DC Impairs the Abmentioning
confidence: 99%
“…Adenoviral vectors encoding OVA or GFP were prepared, purified, and titrated as described previously (19). Ag-specific T cell responses…”
Section: Virus Vectorsmentioning
confidence: 99%